Notes on Street Work in 19th century Salvador (Research, Society and Development, 2020)
The objective of this article is to analyze the street work in the city of Salvador and its developments on urbanity in the 19th century, using the analytical method of the historical and dialectical method, which starts from the fundamental concept that the world cannot be considered a complex of finished and immutable things, but a process of complexes and a process in permanent construction. The main results suggest that the greater presence of blacks in the city of Salvador and the attempts to generate “control and order” by the State, significantly changed the urbanity of the Bahian capital in the second half of the 19th century, leaving rooted problems of social, economic, political, environmental and urban, few attenuated until contemporary times.